Aggressive Great Tits Parus major: starved birds or belonging to a different population? - Ryttman, Hans (Ornis Svecica, 2017)
During autumn 2016, bird ringing stations in east Sweden observed Great Tits Parus major with extremely aggressive behaviour. They attacked smaller birds such as Goldcrests Regulus regulus, killed them and ate the brain or the content of the belly. I examine with data from Ottenby Bird Observatory two explanations: the birds were exhausted after migration and very hungry or they were birds from an eastern population where aggressive behaviour has been suggested to be more common. Fat index and body mass did not indicate low energy stores and the weather was stable with wind from the east so the ﬁrst explanation was not supported. Unfortunately, wing length cannot be used to differentiate between Swedish and more eastern populations so also the second explanation could not be supported. However, Great Tits from eastern parts of north Europe moult their alula earlier than birds from Sweden. The next time aggressive Great Tits are observed, bird ringers should check the moulting stage of the alula in order to determine their origin.